Application research of steel fiber rubber regenerated concrete engineering. Issue 1 (June 2020) - Chen, Yanyan; Liang, Xiaoguang; Liang, Lijun
Abstract: With the booming development of China's building industry, the recycling of building materials can achieve the effect of reducing energy consumption. For the construction and development of rural areas, rural roads and small water conservancy projects are also being gradually optimized and transformed, in which a lot of waste building materials will be generated. With the progress of science and technology and the in-depth research on regenerated concrete, the regenerated concrete began to be promoted everywhere. This paper elaborates the performance of the new steel fiber regenerated concrete rubber, considered from the aspects of reducing engineering cost and shortening the construction period, discusses application of regenerated concrete to rural road construction, small water drains and other projects, so as to provide a reference for the use of renewable resources in rural areas, and promoting the development of more scientific and ecological construction industry.